divide 2x by 2 = x
Now multiply (x + 1)(x - 2)(x)
(x + 1)(x - 2) = x^2 - x - 2
Multiply the above times x for a final answer of
x^3 - x^2 - 2x
or x cubed minus x squared minus 2x
2006-10-05 15:01:37
·
answer #1
·
answered by AskOnlyMe 3
·
0⤊
0⤋
For all real numbers x:
2x(x + 1)(X - 2)/2 = x(x + 1)(x - 2) = x(x² - x - 2) = x³ - x² - 2x
2006-10-05 16:40:35
·
answer #2
·
answered by Jerry M 3
·
0⤊
0⤋
(x+1)(x-2)(2x) = (x+1)(x-2)*2*(x) = 2(x+1)(x-2)(x)
So dividing by two just makes the 2 go away, making:
(x+1)(x-2)(x)
2006-10-05 15:10:50
·
answer #3
·
answered by husam 4
·
0⤊
0⤋
4x +1-2=4x +-1 divided by 2
2006-10-05 16:02:12
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2x-1
2006-10-05 15:02:50
·
answer #5
·
answered by padreperson1 2
·
0⤊
0⤋
x^3-x^2-2x
2006-10-05 15:00:09
·
answer #6
·
answered by Davo 2
·
0⤊
0⤋
(x+1)(x-2)(2x) / 2
= (x+1)(x-2)(x)
=(X^2 +X -(2X) -2)(X)
=(X^2-X-2)(X)
=X^3-X^2-2X
2006-10-05 15:22:26
·
answer #7
·
answered by safrodin 3
·
0⤊
0⤋
what are you trying to figure out the answer or what x is you should right that as more details
2006-10-05 15:01:30
·
answer #8
·
answered by Alexis 3
·
0⤊
0⤋
x3 -x2-2x
2006-10-05 15:04:00
·
answer #9
·
answered by prakashanand 2
·
0⤊
0⤋